2014
DOI: 10.1016/j.jpainsymman.2013.03.013
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Randomized Trials: Immediate Stent Placement vs. Surgical Bypass in the Palliative Management of Malignant Biliary Obstruction

Abstract: Context Many patients with unresectable pancreatic and peripancreatic cancer require treatment for malignant biliary obstruction. We performed a meta-analysis of randomized trials comparing immediate biliary stent placement and immediate surgical biliary bypass in patients with unresectable pancreatic and peripancreatic cancer. Objectives To conduct a meta-analysis of the English language literature (1985 through 2011) comparing those two treatments and analyze hospital utilization patterns. Methods After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0
10

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(48 citation statements)
references
References 26 publications
1
37
0
10
Order By: Relevance
“…Thus, the patients with advanced un-resectable tumors should undergo palliative therapy like biliary duct decompression in order to relieve pruritus and cholestasis. Treatment of obstructive jaundice leads to dramatic improvement in quality of life of the affected patients [21][22][23][24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the patients with advanced un-resectable tumors should undergo palliative therapy like biliary duct decompression in order to relieve pruritus and cholestasis. Treatment of obstructive jaundice leads to dramatic improvement in quality of life of the affected patients [21][22][23][24][25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…2 Meta-analyses of studies comparing endoscopy and surgery for malignant BO revealed that recurrence of BO was significantly less in biliary bypass compared to biliary stent. 24,25 With regards to GOO recurrence, studies showed that incidence rate ranges from 0% to 4.8%. 6,7,9,10,14,15,22 In addition, Hamada et al 2 reported that dysfunction of the duodenal stent was observed in 21% of the patients.…”
Section: Perioperative Outcomesmentioning
confidence: 99%
“…23 When ERCP fails, percutaneous drainage, surgical bypass, and EUS-guided biliary drainage (EUS-BD) are alternative options. [24][25][26] The rates of technical and clinical success have been high with EUS-BD (86%-98% and 88%-94%, respectively), although complication rates have been high as well (9%-26%). [27][28][29][30][31] To potentially improve success, LAMS have been developed and are now being used for choledochoduodenostomy (CD), gallbladder decompression, and cholecystoenterostomy.…”
Section: Bile Duct Drainagementioning
confidence: 99%